A clinical study of lens-induced glaucoma and its outcome after cataract surgery - Preethi G; Pranitha Prabhu; Shweta Sulabh; Appineni Mounika; Battula Bhavyasree (Asian Journal of Medical Sciences, 2024)
Background: Lens-induced glaucomas (LIGs) occur due to the lens’s size, position, or inflammation, causing either open-angle or angle-closure mechanisms. These conditions vary clinically, and understanding their effect on post-operative cataract surgery outcomes is crucial for achieving better visual results. Aims and Objectives: The aim of the study was to evaluate the characteristics, risk factors, and their consequences in LIG on post-operative visual outcome, intraocular pressure, inflammation, and optic disc changes. Materials and Methods: Patients diagnosed with LIG between December 2019 and April 2021 underwent cataract surgery and were assessed pre-and postoperatively for visual outcomes, intraocular pressure (IOP), inflammation, and optic disc changes. Results: During the 18-month study, 2700 cataract cases attended the outpatient department at Oxford Medical College, Bangalore. Among them, 50 cases (1.85%) were diagnosed with LIG. The age range was 37–75 years, with a mean of 60.02 (61.70 years for females, 58.04 years for males). Best-corrected visual acuity (BCVA) of 6/12 or better was achieved in 48% of cases, while severe inflammation resulted in BCVA below 6/60 in 69.23%. Elevated IOP was noted in cases with symptoms lasting 2–4 weeks (39.67 mmHg). Glaucomatous disc damage affected 36% of cases, more common in phacomorphic glaucoma (54%) than phacolytic (28%), and significantly correlated with symptom duration over 2 weeks (P<0.01). Conclusions: Planned small incision cataract surgery with intraocular lens implantation along with minimal tissue handling and a good follow-up protocol with efficient management of complications and inflammation play a major role in management and allow for good visual outcome and fewer complications post-surgery.